2021
DOI: 10.1016/j.jaci.2021.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Using data from food challenges to inform management of consumers with food allergy: A systematic review with individual participant data meta-analysis

Abstract: Background: Eliciting doses (EDs) (eg, ED 01 or ED 05 values, which are the amounts of allergen expected to cause objective symptoms in 1% and 5% of the population with an allergy, respectively) are increasingly being used to inform allergen labeling and clinical management. These values are generated from food challenge, but the frequency of anaphylaxis in From a the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…Patel et al 19 recently published a systematic review of over 3000 DBPCFCs to peanut. This analysis found that approximately 4.5% (95% CI: 1.9%-10.1%) of individuals who reacted to ≤5 mg of peanut protein and 4.2% (95% CI: 0.7%-22.3%) of individuals who reacted to ≤1 mg with objective symptoms experienced anaphylaxis (exposures that approximate to the upper limit of the 95% CI for the amount of allergen expected to cause objective symptoms in 1% of the population with that allergy [ED 01 ] and ED 05 for peanut, respectively).…”
Section: Peanutmentioning
confidence: 99%
See 4 more Smart Citations
“…Patel et al 19 recently published a systematic review of over 3000 DBPCFCs to peanut. This analysis found that approximately 4.5% (95% CI: 1.9%-10.1%) of individuals who reacted to ≤5 mg of peanut protein and 4.2% (95% CI: 0.7%-22.3%) of individuals who reacted to ≤1 mg with objective symptoms experienced anaphylaxis (exposures that approximate to the upper limit of the 95% CI for the amount of allergen expected to cause objective symptoms in 1% of the population with that allergy [ED 01 ] and ED 05 for peanut, respectively).…”
Section: Peanutmentioning
confidence: 99%
“…Patel et al 19 analyzed data from 534 individuals who underwent at least 2 peanut-DBPCFCs over time, to assess the reproducibility of thresholds and recurrence of anaphylaxis in peanut-allergic individuals. Although the intraindividual variability in ED varied by up to 3-log, in the majority 71.2% (95% CI: 56.2%-82.6%) of individuals, this was limited to a half-log change—equivalent to a single dosing interval when using a PRACTALL-style semilogarithmic dosing regimen.…”
Section: Reproducibility Of Thresholds and Likelihood Of Anaphylaxismentioning
confidence: 99%
See 3 more Smart Citations